Diversity of Endophytic Fungi Isolated from Prunus yedoensis and Their Antifungal Activity Against Wood Decay Fungi - Misong Kim; Manh Ha Nguyen; Sanggon Lee; Wonjong Han; Minyoung Kim; Hyeongguk Jeon; Jinheung Lee; Sangtea Seo; Namkyu Kim; Keumchul Shin (Microorganisms)
Endophytic fungi play a vital role in protecting and promoting the growth of their host plants. The diversity of fungal endophytes has been documented across different host plant species and varies depending on factors such as the species of the host, ecological conditions, and the health status of the plant. We isolated endophytic fungi from Prunus yedoensis trees with different decay rates. A total of 31 species were isolated from decayed trees, while 33 species were obtained from healthy trees. The number of endophytic fungi exhibiting antifungal activities against wood decay fungi was higher in healthy trees, with 10 species showing activity compared to only 1 species from decayed trees. Endophytic fungus Fusarium acuminatum (BEN48) had the highest inhibition rates against Trametes versicolor, Ganoderma gibbosum, and Vanderbylia fraxinea. Heating conditions did not significantly affect the inhibitory ability of the culture filtrate from BEN48 on wood decay fungi. At 50% concentration, the inhibitory abilities of the culture filtrates against Trametes versicolor, Ganoderma gibbosum, and Vanderbylia fraxinea were 96.5%, 64.1%, and 92.7%, respectively. The inhibitory effects against Trametes versicolor decreased at concentrations of 30% and 10%, resulting in inhibition rates of 83.7% and 50.8%, respectively. For Ganoderma gibbosum, the inhibition rate reduced to 52.6% at 30% concentration and 24.5% at 10% concentration. For Vanderbylia fraxinea, there was no significant difference between the 30% and 10% concentrations, and the inhibition rates for both concentrations were high, measuring 89.9% and 88.8%, respectively. Hence, Fusarium acuminatum (BEN48) has promise as a biocontrol agent for managing wood decay fungi.